Dynamic Characteristics Analysis of a Coupled Multi-crack Rotor System. Issue 1 (1st March 2022) - Xiong, Libo; Hua, Chunrong; Yang, Funing; Dong, Dawei; Ouyang, Huajiang
Abstract: This paper establishes a coupled model for multi-crack rotor using Timoshenko beam element with six degrees of freedom, and derives the stiffness matrix in the equations of motion accounting for the coupling between multiple cracks (the interaction between cracks). Then the effects of crack orientation angles (the relative angle between cracks, γ) on dynamic characteristics of the coupled multi- crack rotor near 1/3 and 1/2 subcritical speeds are analysed. The coupling between cracks induces more complex nonlinear dynamic characteristics such as large magnitudes of the super-harmonic components, which can be used as the indicators of early crack and for multi-crack identification. This work has a promotive significance for the application of the model-based method in the field of multi-crack detection of actual rotors.